2014
DOI: 10.1002/j.1681-4835.2014.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging E‐Health for Future‐Oriented Healthcare Systems in Developing Countries

Abstract: Health IT has become a driving force for health institutions to embrace holistic integration so as to offer high-quality diagnoses and to provide solutions designed to assist medical personnel to improve patients' healthcare. However, success of integrating IT in healthcare has been seen mainly in developed countries. Health institutions in developing and least developed countries are still being challenged by many factors that have hindered the successful integration of IT in healthcare. Readiness has been on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The findings also revealed that digital health components such as telemedicine/tehealth, e-health and m-health were regarded as essential components for the development of a digital health innovation ecosystem for the Namibian context. This is consistent with other studies which indicate that telemedicine (Cilliers & Flowerday, 2014), e-health (Kalema & Kgasi, 2014), and m-health (Noutat et al, 2016) have been considered important in developing countries.…”
Section: Roundsupporting
confidence: 92%
“…The findings also revealed that digital health components such as telemedicine/tehealth, e-health and m-health were regarded as essential components for the development of a digital health innovation ecosystem for the Namibian context. This is consistent with other studies which indicate that telemedicine (Cilliers & Flowerday, 2014), e-health (Kalema & Kgasi, 2014), and m-health (Noutat et al, 2016) have been considered important in developing countries.…”
Section: Roundsupporting
confidence: 92%
“…e-Health uses information and communication technologies for diagnosing and treating patients and promoting a healthy lifestyle (primary prevention), conducting research, training health professionals, tracking diseases and monitoring public health to improve or create conditions for provision of health services and health care [21], [22], [23].…”
Section: е-Healthmentioning
confidence: 99%
“…The adoption of e-health system in hospitals refers to using technology system for business activities (e-business), accordingly, e-health adoption was derived from business-oriented use [8] related to interbusiness communication, coordination's and collaboration. Again, adoption also refers to the nature of system use [15] based on functional and expected purposes. In the meantime, the readiness construct in using ehealth system was derived from [9,16] which is measured through the relative status of health institutions and systems' users in adopting ICT and information systems.…”
Section: A Electronic Health Information System (His)mentioning
confidence: 99%